Teaching clean and healthy living habits (PHBS) during the Covid-19 epidemic at Plosogede 1 Elementary School - Nurfina Dian Kartikawati; Risty Wisma Oktaberliani; Arbinendra Fajar Sidiq; Alfansuri Mualana Rusli; Pamungkas Budi Handoyo; Rafliyanto Rafliyanto; Fitriana Yuliastuti (Universitas Muhammadiyah Magelang, 2024)
Program Hidup Bersih dan Sehat (PHBS) is an initiative designed to improve the health and well-being of the community. Primary schools serve as the foundation for children's development, and the school environment plays a crucial role in shaping clean and healthy living habits from an early age. The purpose of this community service activity is to enhance the knowledge and understanding of students at State Elementary School 1 Plosogede about Clean and Healthy Living Behaviors (PHBS). This activity is carried out by providing PHBS socialization in the era of the Covid-19 endemic using methods such as lectures, discussions, Q&A sessions, and demonstrations. The results of the activity show an increase in students' knowledge, attitudes, and skills, with the expectation that they can improve their behavior in terms of PHBS. The evaluation results indicate that approximately 26 (74.28%) students received a score of 100, while 9 (25.71%) students received a score of 80.